Estudio de la producción y actividad de proteínas tipo hidrofobinas y quitinasas de Lecanicillium lecanii en cultivos en sustrato sólido y sumergido - Rocha Pino, Zaizy (Universidad Autónoma Metropolitana, 2014)
Lecanicillium lecanii is an entomopathogenic fungus used commercially as a biopesticide in agriculture and horticulture. However, there is scarcity of information about how L. lecanii production of hydrophobins-like proteins (HfbLs) and chitinases are required for their development and enzymes related to pathogenic activity. Therefore, this study evaluated the effect of the hydrophobicity of the conditions culture, such as culture type, support type and carbon source type on the chitinolytic activity, and the production and surface activity of hydrophobins-like proteins (HfbLs) from L. lecanii. The hydrophobicity as result of extrinsic factors such as the culture type, for example, submerged culture, SmC (hydrophilic) and SSC (using PUF, hydrophobic), as well as the carbon source (for example, the chitin, insoluble in water and fructose, soluble in water) had significant effect on the chitinases and class I Hfb production of L. lecanii. SSC added with colloidal chitin as carbon source increased the β- N- acetyl hexosaminidases and Hfbs production ca. 3- and 10-folds, respectively, compared with the submerged culture. Interestingly, in this study showed that the chitin as carbon source acts as inductor of chitinases, as well as also to hydrophobins, it is due to the hydrophobins obtained from SSCchitin cultures showed surface activity to reduce the hydrophobicity of teflon (ca. 50 %), while hydrophobins from SSC added with fructose showed not surface activity on Teflon. Based on these results, the investigation moved forward on the research question of how the hydrophobicity of support type and chemical caracteristics of chitin used in SSC could affect the production and activity of hydrophobins of L. lecanii. This doctoral thesis showed that L. lecanii was able to produce class I and class II HfbLs in solid substrate culture (SSC) added with colloidal chitin as carbon source, the inert supports tested were perlite (P) and polyurethane (PUF). The purity and physicochemical properties as the degree of acetylation (DA) of the chitin, it had significant effect on the production of class I HfbLs of L. lecanii in SSC with PUF. Furthermore, it was observed that the hydrophilic character of the perlite and the hydrophobicity of the polyurethane were significant factors for the production and surface activity of the fungal HfbLs. The class I HfbLs were produced only in cultures with hydrophobic support, PUF, (302.1 ± 14.8 µg HfbL mL-1 ), and these showed surface activity to reduced ca. 50 % the hydrophobicity of teflon. The HfbLs class II were produced in cultures with either both supports, PUF or P, however, HfbLs produced in SSC with P were ca. 3-folds higher than in SSC with PUF. The class II HfbLs were able to reduce ca. 25 % the hydrophobicity of teflon and to reduce ca. 50 % of the surface tension of water. The hydrophobicity of volatile organic compounds (VOCs) used as carbon sources in submerged cultures of L. lecanii also showed significantly influence on the production of chitinases and HfbLs. L. lecanii showed be able to grow and consume n-hexane or toluene with or without addition of colloidal chitin as carbon source in submerged culture (SmC). L157 strain showed highest consumption of n- hexane (55.6 %) and toluene (52.9 %) as sole carbon source. In SmC cultures added with chitin and hydrocarbons (MCHT or MChH), the strain L157 showed ability to produce endochitinases and N- acetyl hexosaminidases, also, it increased ca. 10-folds their HfbLs class I production (548.6 ± 26.3 µg Hfb mL-1 protein) compared with cultures added with chitin as sole carbon source (57.4 ± 4.7 µg Hfb mL-1 protein). The hydrophobicity of VOCs tested. Also, it had significant effect on the surface activity of class I HfbLs. Class I HfbLs from MChT culture reduced ca. 48 % the hydrophobicity of teflon, in contrast to HfbLs from MChH (ca. 10 %). This study allowed us to observe the close relationship between the chitinases and hydrophobins production of L. lecanii. Noteworthy, the hydrophobicity of the culture, the support and the carbon source type were key elements to the production and surface activity of hydrophobins-like proteins, while the chitin was essential for the production of HfbLs with surface activity. The information obtained about the hydrofobicity effect on the chitinases and HfbLs production, allows us to deepen our knowledge about the development and pathogenesis of L. lecanii. Furthermore, it was possible to establish a method of transformation of L. lecanii using phosphinothricin (PPT) as a selective agent (bar gene), which could facilitate for studies about their development and interaction with the environment. Based on the above, this study could continue the purification, structural analysis and interaction of this fungus on different surfaces and with the study the involvement of HfbLs in the fungal development.; Lecanicillium lecanii es un hongo entomopatógeno usado comercialmente como agente de control biológico en agricultura. Sin embargo, poco se sabe sobre su producción de proteínas tipo hidrofobinas (HfbLs) y quitinasas, las cuales son requeridas para su desarrollo y actividad patogénica. En virtud de lo anterior, en esta tesis de doctorado se estudió diversos factores que afectan a la producción de dichas proteínas, tales como, el tipo cultivo, de soporte y fuente de carbono. Asimismo, se determinó el efecto sobre la actividad superficial de HfbLs. La hidrofobicidad resultado de factores extrínsecos, como el tipo de cultivo, tal es el caso del cultivo sumergido SmC (hidrofílico) y SSC (utilizando PUF, material hidrofóbico), la fuente de carbono (por ejemplo, la quitina que es insoluble en agua y la fructosa que es soluble en agua), influyeron significativamente sobre la producción de quitinasas e hidrofobinas de clase I de L. lecanii. El crecimiento de L. lecanii en SSC y el uso de quitina coloidal como fuente de carbono favoreció la producción de β-N-acetilhexosaminidasas e hidrofobinas ca. 3 y 10 veces, respectivamente, en comparación con el SmC. Interesantemente, en este estudio se observó que si bien la quitina es un inductor de quitinasas, también tuvo efecto significativo sobre la actividad superficial de hidrofobinas. La hidrofobina clase I obtenida de SSC con quitina mostró actividad superficial al reducir la hidrofobicidad del teflón (ca. 50 %), lo cual no ocurrió con las proteínas producidas en SSC adicionado con fructosa. Las observaciones anteriores permitieron el planteamiento de la pregunta de investigación sobre cómo la hidrofobicidad del tipo del soporte y características químicas de la quitina empleada en SSC podrían afectar la producción y actividad de las hidrofobinas de L. lecanii. Los resultados mostraron que L. lecanii fue capaz de producir proteínas tipo hidrofobina clase I y clase II en cultivos en sustrato sólido (SSC) utilizando agrolita (P) o poliuretano (PUF) como soportes inertes adicionados con quitina coloidal como fuente de carbono. La pureza y las propiedades fisicoquímicas, así como el grado de acetilación (DA) de la quitina, influyeron significativamente en la producción de hidrofobinas clase I de L. lecanii en SSC sobre PUF. Además, se observó que el carácter hidrofílico de la agrolita y la hidrofobicidad del poliuretano fueron factores significativos para la producción y actividad superficial de las HfbLs de este hongo. La mayor producción de HfbLs clase I se obtuvo en cultivos con soporte hidrofóbico, PUF, (302.1 ± 14.8 µg HfbL mL⁻¹ ), y mostraron tener actividad superficial al reducir ca. 50 % la hidrofobicidad del teflón. Las HfbLs clase II fueron producidas en ambos soportes, PUF y P, sin embargo su producción en cultivos con agrolita fue ca. 3 veces mayor en comparación al PUF. Las HfbLs clase II mostraron capacidad de reducir ca. 25 % la hidrofobicidad del teflón y ca. 50 % la tensión superficial del agua. Se determinó que la hidrofobicidad de compuestos orgánicos volátiles (COVs) utilizados como fuentes de carbono en cultivos sumergidos tipo microcosmos también influyó significativamente sobre la producción de quitinasas y HfbLs. L. lecanii mostró capacidad de crecer y consumir n-hexano y tolueno con o sin quitina coloidal como fuente de carbono en SmC. La cepa L157 mostró el mayor consumo de n-hexano (55.6 %) y tolueno (52.9 %) al ser utilizados como única fuente de carbono. En SmC adicionados con quitina e hidrocarburos (MChT y MChH), la cepa L157 mostró capacidad de producir endoquitinasas y N-acetil hexosaminidasas e incrementó hasta 10 veces la producción de HfbL clase I (548.6 ± 26.3 µg Hfb mL⁻¹ proteína) en comparación con lo observado en cultivos adicionados con quitina como única fuente de carbono (57.4 ± 4.7 µg Hfb mL⁻¹ proteína). La hidrofobicidad de los COVs probados también afectó la actividad superficial de las HfbLs clase I. La mayor reducción de la hidrofobicidad del teflón fue obtenida con las HfbLs clase I obtenidas de MChT (ca. 48 %) en comparación con las obtenidas de MChH (ca. 10 %). El presente estudio nos permitió observar la estrecha relación entre la producción de las quitinasas e hidrofobinas de L. lecanii. Es destacable observar que la hidrofobicidad del tipo de cultivo, el soporte y la fuente de carbono en el cultivo fueron elementos clave para la producción y actividad superficial de las proteínas tipo hidrofobinas, mientras que el uso de quitina fue esencial para la producción de HfbLs con actividad superficial. Determinar el efecto de la hidrofobicidad sobre la producción de quitinasas y HfbLs de L. lecanii resultó relevante para profundizar nuestro conocimiento sobre el desarrollo y patogénesis del hongo. Además, fue posible establecer un método de transformación de L. lecanii empleando fosfinotricina (PPT) como agente selectivo (gen bar) lo cual podría facilitar los futuros estudios sobresu desarrollo e interacción con el ambiente. Con base en lo anterior, este estudio podría continuar con la purificación, análisis estructural e interacción de este hongo sobre diferentes superficies y con el estudio de la participación de las HfbLs en el desarrollo fúngico.